Can Covenantal Pluralism Grow in Central Asian Soil? Hopes and Hard Lessons from the Religious History of the Region - Olcott, Martha B. (The review of faith & international affairs, 2020)
The history of Central Asia prior to and during the process Islamization both provides a potential grounding for the concept of covenantal pluralism in the region and presents challenges to its fruition. While Central Asia has always been home to diverse religious practices, an orthodox interpretation of Islam was privileged over these. Non-Muslim religious minorities could expect protection, but limitations under Abbasid rule; heterodox Muslims were seen as security threats. The modern republics of Central Asia have extended state control over Islam, continue to privilege it, and use security as a justification to persecute Muslim groups outside of their control in addition to some Protestant sects.